Improving The Accuracy of 3D Geologic Subsurface Models - MacCormack, Kelsey (My University, 2010)
This study investigates ways to improve the accuracy of 3D geologic models by assessing the impact of data quality, grid complexity, data quantity and distribution, interpolation algorithm and program selection on model accuracy. The first component of this research examines the impact of variable quality data on 3D model outputs and presents a new methodology to optimize the impact of high quality data, while minimizing the impact of low quality data on the model results. This 'Quality Weighted' modelling approach greatly improves model accuracy when compared with un-weighted models.
The second component of the research assesses the variability and influence of data quantity, data distribution, algorithm selection, and program selection on the accuracy of 3D geologic models. A series of synthetic grids representing environments of varying complexity were created from which data subsets were extracted using specially developed MA TLAB scripts. The modelled data were compared back to the actual synthetic values and statistical tests were conducted to quantify the impact of each variable on the accuracy of the model predictions. The results indicate that grid complexity is the predominant control on model accuracy, more data do not necessarily produce more accurate models, and data distribution is particularly important when relatively simple environments are modelled. A major finding of this study is that in some situations, the software program selected for modelling can have a greater influence on model accuracy than the algorithm used for interpolation. When modelling spatial data there is always a high level of uncertainty, especially in subsurface environments where the unit(s) of interest are defined by data only available in select locations. The research presented in this thesis can be used to guide the selection of modelling parameters used in 3D subsurface investigations and will allow the more effective and efficient creation of accurate 3D models.
Keywords: 3D; geologic; subsurface model; data quality